2005
DOI: 10.1897/04-447r.1
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine (sexual) disruption is not a prominent feature in the pike (Esox lucius), a top predator, living in english waters

Abstract: The high incidence of intersex roach (Rutilus rutilus) in some United Kingdom rivers that has been associated with exposure to sewage treatment works (STWs) effluent led us to hypothesize that top predator fish also may be affected by estrogenic chemicals, because they are likely to bioaccumulate lipophilic compounds through a predator-prey relationship. To investigate this possibility, pike (Esox lucius) were sampled both upstream and downstream of STWs and then examined for total estrogenic activity of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In contrast, Körner et al (2005) observed small nests fi lled with all stages of spermatogenesis occupying less than 1 % of the gonads. This fi nding, with a prevalence up to 27 %, is consistent with fi eld observations in Danish brown trout (Christiansen and Plesner, 2001), but also whitefi sh (Mikaelian et al, 2002) and pike (Vine et al, 2005), reporting a prevalence between 12 % and 26 %.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Körner et al (2005) observed small nests fi lled with all stages of spermatogenesis occupying less than 1 % of the gonads. This fi nding, with a prevalence up to 27 %, is consistent with fi eld observations in Danish brown trout (Christiansen and Plesner, 2001), but also whitefi sh (Mikaelian et al, 2002) and pike (Vine et al, 2005), reporting a prevalence between 12 % and 26 %.…”
Section: Discussionsupporting
confidence: 91%
“…Kipfer et al 2009 (and intersex) gonad tissues (Jobling et al 1998, van Aerle et al 2001, Noaksson et al 2001, Kavanagh et al 2004, Hanson 2009). Hermaphroditic histological changes in the ovaries have also been reported in northern pike (Dominguez et al 1989, Vine et al 2005. However, the results pre sented in the present pa per are the first data about extreme alterations of ovaries in northern pike, the top pre dator in freshwater food webs.…”
Section: Discussionsupporting
confidence: 51%
“…This is a possible aetiology of this phenomenon for northern pike as well, particularly given that 2 different environments were considered, and only one was subjected to industrial pollution (from the wastewater treatment plant). Also, Vine et al (2005) reported that the pollution originating from the treatment plant did not cause gonadal malformation in northern pike. However, to support the hypothesis that improper hatchery management can cause genetic changes resulting in gonadal alterations, a detailed evaluation is needed of the protocols in hatcheries where the restocked fry was produced as well as an evaluation of spawner origin and condition.…”
Section: Discussionmentioning
confidence: 99%
“…This is because, although cumulative and persistent weak estrogenic chemicals are almost certainly present in the freshwater environment, their effect would be very difficult to demonstrate in an environment dominated by shortlived but nevertheless far more potent compounds emanating from sewage treatment works and factories. However, one study ( Another study (Vine, Shears, van Aerle, Tyler, & Sumpter, 2005), that looked for effects in a top predator, the pike (Esox lucius) preying on estrogen-contaminated roach, found that, although the bile of male pike caught downstream had significantly more estrogenic activity than that of male pike caught upstream, there was no significant difference in VTG concentrations. Only two out of fifty-two male pike had detectable VTG in their plasma.…”
Section: What Is the Most Likely Route Of Exposure?mentioning
confidence: 99%